Description of Characteristics of Typhoid Fever Sufferers in Children Aged 5-14 Years at RSU Royal Prima Medan for the Period August 2022-February 2023 - Dhawy Dermawan, Dzaky; Fadillah, Qori; Budi, Andre (Jurnal Multidisiplin Indonesia, 2024)
Infectious diseases are still a public health problem, especially in developing countries. One of the infectious diseases is typhoid fever. Typhoid fever is an acute infection of the small intestine with symptoms of fever lasting more than one week, which can cause digestive disorders and reduce the level of consciousness. This research aims to analyze the characteristics of typhoid fever sufferers in children aged 5-14 years at RSU Royal Prima Medan from August 2022 - February 2023. The type of research used in this research is a qualitative description with a cross-sectional design. The population used was 46 medical records of typhoid fever sufferers in children aged 5-14 years at RSU Royal Prima Medan from August 2022 - February 2023. The sampling technique used in this research used total sampling, while the number of samples used was 46 records. Medical treatment for typhoid fever patients. Data analysis uses univariate analysis. The results of the study showed that the number of typhoid fever sufferers in children aged 5-14 years at RSU Royal Prima Medan from August 2022 – February 2023 was 46 children, 27 of the sufferers were predominantly male while 19 were female. All typhoid fever sufferers in this study experienced accompanying symptoms of fever, nausea, vomiting, and diarrhea; only five typhoid fever sufferers, or 10.9%, were accompanied by additional accompanying symptoms in the form of abdominal pain. Normal body weight in male patients was 19 patients, and abnormal body weight was eight patients. Normal body weight in female patients was eight patients, and abnormal body weight was 11 patients. All typhoid fever sufferers received RL and NaCL therapy, only 11 sufferers received additional Cefixime therapy, and only 32 sufferers received additional Cefriaxone therapy. August 2022 – February 2023 is > 3 days.